Effects of BIOWISH MultiBio 3P on Growth Performance and Carcass Characteristics of Grow-Finish Pigs - M. B. Menegat; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
This study was conducted to determine the effects of a multi-species direct-fed microbial product based on lactic acid bacteria andBacillus subtilison growth performance and carcass characteristics of grow-finish pigs. A total of 1,188 pigs (PIC 359 × 1050; initially 57 lb BW) were used in a 121-d growth trial with 27 pigs per pen and 22 pens per treatment. Pigs were allotted to treatments based on initial body weight (BW) in a randomized complete block design. The two experimental diets were Control and Biowish (BIOWISH MultiBio 3P, BIOWISH Technologies Inc., Cincinnati, OH). The diets were based on corn, distillers dried grains with solubles, and soybean meal, and fed in four dietary phases. The probiotic BIOWISH MultiBio 3P was included in the diet at 1.1 lb/ton at the expense of corn. Overall, from d 0 to 121, pigs fed the control diet had greater average daily gain (ADG) (P<0.024) and final BW (P<0.001) compared to pigs fed the Biowish diet. There was no evidence for differences in average daily feed intake (ADFI) and feed efficiency (F/G) between dietary treatments. The difference in final BW resulted in heavier (P<0.026) hot carcass weight (HCW) in control pigs compared to Biowish pigs, but no evidence for differences was observed in carcass yield, backfat, loin depth, and lean percentage between dietary treatments. In conclusion, the inclusion of BIOWISH MultiBio 3P in growing-finishing diets reduced ADG in this commercial study. This response was not expected, but could be related to inclusion rate or other factors not identified in this study. This warrants further research to better characterize the effects of this probiotic on pig performance.
Keywords: feed additive; finisher; probiotic; swine